Unexpected reactivity of “GaI” towards N,N′-diaryl-β-diketiminate tin(II) chloride: Synthesis, X-ray diffraction analysis and DFT studies - Ibarra Rodríguez, Marisol; Jiménez Pérez, Víctor Manuel; Muñoz Flores, Blanca M.; Waksman Minsky, Noemí Herminia; Ramírez, Rosalba; Sánchez, Mario; Hernández Ahuactzi, Iran F. (2015)
Reaction of the [HC(CMeNAr)2]SnCl (Ar = 2,4,6-Me3C6H2) with ‘‘GaI” in THF provided an unexpected transhalogenation reaction product [HC(CMeNAr)2]SnI. The crystal structure shows a tin(II) ion with a distorted tetrahedral pyramidal geometry. Theoretical calculations, using density functional theory (B3LYP), suggest the probable reaction mechanism for transhalogenation. The activation energy for moving from reactant ([HC(CMeNAr)2]SnCl to product [HC (CMeNAr)2]SnI) is only 10.2 kcal/mol. The chloride ion is displaced by the iodine ion, probably by the help of the gallium atom when it is coordinated to the chlorine atom.